Bacteriological Spectrum of Sputum in Acute Exacerbation of Chronic Obstructive Pulmonary Disease (COPD) - Khatun, Tahera; Das, Aparna; Banik, Gobinda Chandra; Dhar, Uma; Sharif, Mohiuddin; Yeasmin, Kayanat; Debnath, Suchismita (Journal of Medicine, 2022)
Background: Acute Exacerbation of COPD (AECOPD) is natural course of Chronic ObstructivePulmonary Disease (COPD), where bacterial infection is the major cause. Bacterial infection worse thesign symptoms of the patients and ultimately increase morbidity & mortality. Methods: This is a cross-sectional observational study. 100 clinically diagnosed cases of AECOPD agedbetween 18 and 85 years were included in the study. The sputum specimen was processed by conventionalMethods and subjected to culture and sensitivity in standard laboratory. Results: The prevalence of AECOPD was more common in age group of fifty-six to sixty- five years(38%) with ratio between male and female of 4.6:1. The prevalence of Gram-negative bacteria was 65.21%and Gram-positive bacteria was 34.79%. K. pneumoniae was the commonest bacteria isolated (36.95%)followed by P. aeruginosa (21.73%), S. aureus (15.21), S. pneumoniae (10.86), S. pyogenes and E. coli(6.52%), MRSA (2.17%). The drug sensitivity reveals that 79.55% of the isolates were sensitive to Amikacin(79.55%) followed by Azithromycin (70.45%), Amoxy clavulanic acid (68.18%) and Ciprofloxacin (63.63%). Conclusion: Repeated exacerbation and hospital admission leads to a major impact on the quality of life ofpatients with COPD. Antibiogram helps in screening resistant pathogens and prescribing right treatment protocol. J MEDICINE 2022; 23: 30-35